Association of the genetic polymorphisms of metabolizing enzymes, transporters, target receptors and their interactions with treatment response to olanzapine in chinese han schizophrenia patients. (November 2020) - Yan, Pan; Song, Mingfen; Gao, Bing; Wang, Shuqi; Wang, Shengdong; Li, Jing; Fang, Haihong; Wang, Chengpeng; Shi, Jianfei
Highlights: To the best of our knowledge, this is the first comprehensive analysis of the relationships between genetic polymorphisms of drug metabolizing enzymes, transporters and target receptors and treatment response to olanzapine fully considering gene-gene interaction in the chinese han population. All patients in the present study were diagnosed with paranoid schizophrenia which is the most common type of schizophrenia as the research subjects to reduce the heterogeneity of the samples. Our subjects consisted of chinese han inpatients, so that the groups had homogenous ethnic background and the environmental factors influencing symptomatology were minimized. Our findings could partially explain the different olanzapine outcome and provided evidence for clarifying the predictive indicators of olanzapine response in further. ABSTRACT: Olanzapine is an atypical antipsychotic drug that has been increasingly used for treatment in schizophrenia. It has been observed that olanzapine responses in schizophrenia patients vary individually, but the reason has not been elucidated. In the study, we aimed to comprehensively explore the relationships between olanzapine responses and genetic polymorphisms of drug metabolizing enzymes, transporters and target receptors, and so as to interpret the reason of good and poor responses of olanzapine. A total of 241 Chinese Han paranoid schizophrenia who treated with olanzapine alone for 4 weeks were recruited. The positive and negative symptom scale (PANSS) was used to evaluate the efficacy of olanzapine. The genetic polymorphisms were detected by improved multiple ligase detection reaction (iMLDR). Multivariate logistic regression analysis suggested that the genetic polymorphisms of CYP1A2 rs762551, UGT1A4 rs2011425, ABCB1 rs1045642, DRD2 rs1799732 and rs1799978, 5-HTR2A rs6311 were significantly associated with olanzapine response. Multifactor dimensionality reduction (MDR) analysis showed that there was a negative interaction between CYP1A2 rs762551, ABCB1 rs1045642, DRD2 rs1799978, 5-HTR2A rs6311 and the interaction model was the optimal model. Our findings could partially explain the different olanzapine outcome and provided evidence for clarifying the predictive indicators of olanzapine response in further.